Autonomous English as a second language writing through group-writing transformations / Nalini Arumugam ... [et al.] - Arumugam, Nalini; Supramanlam, Kaarthiyainy; Geraldine, De Melle; Christ Dass, Laura (Research Management Institute (RMI), 2013)
The study investigated the effects of group-writing on learners at an institution of higher learning who worked in cooperative based writing groups (group-writing henceforth) and individually. 117 undergraduates participated in this quasi-experimental study for 14 weeks. The learners were grouped in groups of three or four. A mixed-design approach was employed in data collection. Questionnaires were administered and semi-structured interviews were carried out to elicit information. The results indicated a favourable view of group-writing as an instructional approach in English as a second language (hereafter ESL) writing classrooms. The learners in the group-writing cooperated with each other on assigned tasks. The results revealed that there was a significant difference between the experiment and control groups, whereby the m 39.3 772 value for the experimental group while m 28.1149 for the control group at (0<,05). This obviously shows that the learners in the experimental group have out performed the learners who worked individually. As they had more opportunities to work together, they built a strong perception of group cohesion and responsibility for other's learning which gradually helped them become autonomous writers. This study adds insights into pedagogical approaches used in ESL centres of higher learning and recommendations are suggestedfor further research.